Rate Infiltration Evaluation on Several Land Uses Using Infiltration Method of Horton at Sub DAS Coban Rondo Kecamatan Pujon Kabupaten Malang - Wirosoedarmo, Ruslan; Suharto, Bambang; Hijriyati, Wulan Ruhunnatiqah (Jurnal Teknologi Pertanian, 2009)
The research was done on October until November 2008 in Sub DAS Coban Rondo Pujon Kabupaten Malang.  The aim of the research was to get information about infiltration rate at several land uses, to understand the relationship between the infiltration constant and the factors that influence infiltration process, and to know when infiltration method of Horton can be used to estimate infiltration.The measurement of infiltration in Sub DAS Coban Rondo used double ring infiltrometer with three treatments on eucalyptus land, corn land, and empty land. The removal sample soil was performed to know soil physical characteristic, and later to know the relationship between infiltration constant and soil physical characteristic. The result of this research indicated that at the beginning, infiltration value at eucalyptus land was 13.200 mm/minute, while at corn land was 15.800 mm/minute and 15.133 mm/minute for empty land.  The relationship between infiltration constant and bulk density was the high value of infiltration constant was followed by the low bulk density.  The high infiltration constant was followed by high space pore, water content, and organic matter.  Based on the calculation using Infiltration Method of Horton and infiltration in Sub DAS Coban Rondo with t-test there was no obvious difference at level of 99% with the result that Infiltration Method of Horton can be used to estimate infiltration process.         Keywords: infiltration, land use, infiltration method of Horton